Human Resource Management Strategy to Improve Operational Efficiency in the Hotel Industry: Case Study of Favehotel Rungkut Surabaya - Azzahra, Amanda Nur; Nurhadi, Nurhadi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study examines human resource management strategies at Favehotel Rungkut Surabaya, focusing on operational efficiency improvement through effective workforce optimization. Using a qualitative case study approach, the research analyzes how a budget hotel manages 31 contract employees across 8 departments while maintaining service quality. The findings reveal that implementing work rotation systems, multi-skill training programs, and lean organizational structures contributed to a 27% increase in operational efficiency over two years. Key challenges identified include workload optimization, cross-departmental coordination, and employee competency development. This research provides practical implications for budget hotels in designing effective HR strategies, particularly in resource allocation, competency development, and performance evaluation systems